The effect of strength training on estimates of mitochondrial density and distribution throughout muscle fibres - Chilibeck, P. D.; Syrotuik, D. G.; Bell, G. J. (European Journal of Applied Physiology, 1999)
The purpose of this study was to investigate the effect of strength training (12 weeks, 3 days/week, four lower-body exercises) of young individuals (mean age 23.6 years) on estimates of mitochondrial distribution throughout muscle fibres. A control group (mean age 21.7 years) was followed simultaneously. Skeletal muscle biopsy samples were obtained from the vastus lateralis, pre- and post-training. The regional distribution of subsarcolemmal and intermyofibrillar mitochondrial populations was determined using quantitative histochemical staining of succinate dehydrogenase (SDH) in type I and II muscle fibres. Strength training resulted in significant increases of 26% and 28% in the cross-sectional area of type I and II fibres, respectively (P<0.05). Overall SDH activity decreased by 13% with strength training (P<0.05). The decrease in SDH activity with strength training between fibre types and between subsarcolemmal and intermyofibrillar regions of muscle fibres was not different. Fibre area and SDH activity was unchanged in the control group. We conclude that the muscle hypertrophy associated with strength training results in reduced density of regionally distributed mitochondria, as indicated by the reduction in the activity of SDH.